2019
DOI: 10.19173/irrodl.v20i2.3730
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Demographics and Students’ Motivation as Predictors of Completion of a Massive Open Online Course

Abstract: This paper investigates the degree to which different variables affect the completion of a Massive Open Online Course (MOOC). Data on those variables, such as age, gender, English proficiency, education level, and motivation for course enrollment were first collected through a pre-course survey. Next, course completion records were collected via the Coursera database. Finally, multiple binomial logistic regression models were used to identify factors related to MOOC completion. Although students were grouped a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 33 publications
4
20
0
Order By: Relevance
“…Moreover, some authors have identified different subgroups among MOOC-takers with different profiles in relation to engagement, completion rates, accomplishment, and learning outcomes. For example, Li and Baker (2018) found heterogeneity in behavioral patterns among learners that is expression of different levels of engagement, and different reasons why participants decide to engage (see also Walji, Deacon, Small, & Czerniewicz, 2016;Williams, Stafford, Corliss, & Reilly, 2018;Zhang, Cesar Bonafini, Lockee, Jablokow, & Hu, 2019). In sum, they conclude that in MOOCs the existence of self-defined learning pathways generates the need to apply different measures to discern the way learners are taking advantage of the content of the courses (see also Petronzi & Hadi, 2016;Reilly, Williams, Stafford, Corliss, Walkow, & Kidwell, 2016;Shapiro, Lee, C. H., Wyman Roth, Li, Çetinkaya-Rundel, & Canelas, 2017;Tseng, Tsao, Yu, Chan, & Lai, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some authors have identified different subgroups among MOOC-takers with different profiles in relation to engagement, completion rates, accomplishment, and learning outcomes. For example, Li and Baker (2018) found heterogeneity in behavioral patterns among learners that is expression of different levels of engagement, and different reasons why participants decide to engage (see also Walji, Deacon, Small, & Czerniewicz, 2016;Williams, Stafford, Corliss, & Reilly, 2018;Zhang, Cesar Bonafini, Lockee, Jablokow, & Hu, 2019). In sum, they conclude that in MOOCs the existence of self-defined learning pathways generates the need to apply different measures to discern the way learners are taking advantage of the content of the courses (see also Petronzi & Hadi, 2016;Reilly, Williams, Stafford, Corliss, Walkow, & Kidwell, 2016;Shapiro, Lee, C. H., Wyman Roth, Li, Çetinkaya-Rundel, & Canelas, 2017;Tseng, Tsao, Yu, Chan, & Lai, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study of students' motivation and their completions by Zhang et al (2019) used students' demographics and motivation as predictors of their completion in a MOOC.…”
Section: Motivation Of Studentsmentioning
confidence: 99%
“…However, given the positive impact, there are still some challenges reported in many kinds of literature focused on trying to understand the low completion rates for courses in MOOC platforms (Liu et al, 2019). Analysis of learner behavior in MOOCs mentioned that students who have got the certificate were majority viewed without deep understanding the contents, and some of them were completely skipping (Zhang et al, 2019). This is a pressing issue until recently, mainly for a difficult subject.…”
Section: Moocmentioning
confidence: 99%